BARONGAN BARUNO PATI: PROSES PENCIPTAAN, BENTUK, DAN REPRESENTASI KOLEKTIF - Muhammad, Fahri Reza (Paradigma: Jurnal Kajian Budaya, 2026)
Amidst conservation challenges and a crisis in the regeneration of local arts in Pati, Barongan Baruno emerges as a new artistic creation from Pasinaon Studio in Kertomulyo Village. This research aims to uncover its creation process, form, and the embodiment of local values as a collective representation of the Kertomulyo community. Using a qualitative-descriptive approach, the study finds that Barongan Baruno is a product of conscious and participatory collective creation. Symbolically, it reflects the community's agrarian-maritime identity and Javanese-Islamic acculturation. As a collective representation, this art form serves as a medium for embodying local wisdom, such as the importance of intention, harmony, and unity. This research affirms that communities can actively create cultural products to represent their identity and values, offering a significant foundation for contemporary barongan studies.